Academic evaluation systems. Effects and challenges for research professors - Castillo-Serrano, Gisela; Jiménez-Vásquez, Mariela Sonia (Opción, 2022)
This article shares findings on experiences, meanings and professional experiences of research professors from the Autonomous University of Tlaxcala who challenge access, permanence and promotion for the system and researchers (SNI, ESDEPED, PRODEP). Based on a feminist methodology, a biographical method was chosen through life stories. Co-structured interviews systematized in biograms were carried into through in-depth interviews. The findings include institutional aspects such as job stability, personal situations and support networks when trying to reconcile family life and research out to chronologically outline their lives. Critical incidents were delved.